Dance’s Duet with the Camera: Motion Pictures. Edited by Telory D. Arendell and Ruth Barnes. 2016. London: Palgrave MacMillan. 263 pp. Hardcover $99.99. ISBN 978-1-137-59609-3 - Frasson, Elisa (The International Journal of Screendance, 2019)
A review of Dance’s Duet with the Camera: Motion Pictures edited by Telory D. Arendell and Ruth Barnes.